France : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes economic developments in France during 1990-95. Partner country demand recovered markedly in the course of 1993, following a sharp downturn since the middle of 1992. The surge of exports during the second half of 1993 was followed by a temporary stabilization at a higher level during the first half of 1994. Strong export growth resumed during the second half of 1994. Overall, French exports of goods and nonfactor services increased by almost 6 percent in 1994. A rapid pace of expansion was maintained during the first half of 1995.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet